Improving Student Learning Outcomes in Islamic Education Learning by Using Learning Videos at State Elementary School 29 Tamparungo - Darena (Jurnal Profesi Guru Indonesia, 2024)
This study aims to increase students' faith in the prophets and apostles in Islamic religious education learning by using video. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that learning video can increase faith in the prophets and apostles in Islamic education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 49.61%, the first cycle 67.29% and in the second cycle it increased to 84.76%. Thus, the use of learning video can be used as an alternative to improve student learning outcomes in Islamic education learning.